Sense of Community among the Residents of Gated and Non-Gated Communities in Lahore, Pakistan - Nadeem, Obaidullah; Hameed, Rizwan; Ayyaub, Pernia (Journal of Art, Architecture and Built Environment, 2023)
Planned gated and non-gated communities have appeared rapidly all over the world due to the public amenities and quality of life they offer. It is generally assumed that gated communities provide better security as compared to non-gated communities. However, population growth and urban sprawl have led to many social and physiological issues including the death of old city traditions, community identity, and lack of the sense of community (SOC). Thus, modern urban development faces the challenge of meeting the habitation and social needs of people with lesser face-to-face interaction and more mobile and fluid ways of communication. Lahore is the second largest city of Pakistan. It has experienced the growth of private sector led gated communities over several years. This research aims to compare their physical characteristics, as well as the perception of security, extent of social interaction, and the sense of community among their residents. For this purpose, the data of interviews with the residents of 4 selected gated and non-gated communities of Lahore was collected. The findings revealed that the sense of community is strongly associated with the extent of social interaction in both gated and non-gated communities. Contrary to what the literature generally suggests, this study found a higher sense of security among the residents of non-gated communities than gated communities. Finally, it was concluded that the participation of the residents in community development and management activities would promote more socially cohesive and vibrant communities.